Advances in the design and delivery of peptide subunit vaccines with a focus on Toll-like receptor agonists. (February 2010) - Black, Matthew; Trent, Amanda; Tirrell, Matthew; Olive, Colleen
Considerable success has been made with many peptide antigen formulations, and peptide-based vaccines are emerging as the next generation of prophylactic and remedial immunotherapy. However, finding an optimal platform balancing all of the requirements for an effective, specific and safe immune response remains a major challenge for many infectious and chronic diseases. This review outlines how peptide immunogenicity is influenced by the way in which peptides are presented to the immune system, underscoring the need for multifunctional delivery systems that couple antigen and adjuvant into a single construct. Particular attention is given to the ability of Toll-like receptor agonists to act as adjuvants. A survey of recent approaches to developing peptide antigen delivery systems is given, many of which incorporate Toll-like receptor agonists into the design.